Pervasive Technologies and the Paradoxes of Multimodal Digital Communication - Sandra Petroni (Lea, 2014)
Contemporary societies are greatly challenged by paradoxes in all facets of life. Digital communication encodes and produces meaning by making use of these contradictory relations. In this contribution, three digital paradoxes will be presented. The first paradox is grounded in the process of remediation in digital settings which mirrors a contradictory double logic. Digital culture, in fact, wants both to multiply its media and to eliminate all traces of mediation. The second antinomy has its origins in the new concept of linguistic entropy: a structured information disorder that is regulated by usability and multimodality. In accordance with the second paradox, the third one stems from further processes that are framing, a multimodal resource, and linking, a hypertextual resource.